Enforcement of safety guidelines in factory indsutries: a legal myth? / Faiza Hanna Abd Kadir Aljailani, Kazlinda Anith Mohd Khalid and Nor Subaiha Juhari - Abd Kadir Aljailani, Faiza Hanna; Mohd Khalid, Kazlinda Anith; Juhari, Nor Subaiha (2008)
In Malaysia, 38.7% of the total populations are workers in the labor force. The number of accident that occur among them in Malaysia is quite high due to negligence and. Therefore, there are certain remedies provided for them. One of the remedies is Occupational Safety & Health Act (OSHA). This Act guaranteed the safety, health and welfare of the employees. Besides OSHA, Employees' Social Security Act 1968 (ESSA) was published, also to provide remedies for those workers who suffer injury in manufacturing industry. For foreign workers who work in manufacturing industry, they are covered under Workmen's Compensation Act 1952 (WCA) which also provide them the security in safety, health and welfare.The employees will be given rights to claim for a remedy from SOCSO whenever accident occurs during working hours in the manufacturing industry. The scheme, known as, Employment Injury Insurance Scheme will protect employees who suffered temporary or permanent disablement injury .In order for them to claim compensation under SOCSO, they must make an application to SOCSO and satisfy the rules required by ESSA. Every employee has duty to ensure safety, health and welfare for his workers at the workplace. Whoever failed to fulfill any provisions in OSHA, he shall be liable to pay fine not exceeding RM10 000 or imprisonment for a term not exceeding one year or both, as stated under Section 51 of the OSHA.